2017
DOI: 10.3199/iscb.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among Egyptian species of Anthemideae (Asteraceae) using ITS markers

Abstract: The relationships of 12 species in six genera in the tribe Anthemideae of the Asteraceae such as Achillea santolina, A. fragrantissima, Anacyclus monanthos, Cotula anthemoids, C. barbata, C. cinerea, Glebionis coronaria var. discolor, Matricaria recutita and M. aurea collected in different localities in Egypt and have been addressed based on polymophism in ITS sequence. Phylogenetic relationships were constructed using bioinformatic tools based on molecular data of ITS sequence. Studied taxa showed cryptic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The obtained results showed that the G. coronaria and G. discolor can be distinguished using these markers, but further studies with a higher number of molecular markers are needed to confirm it. The genetic difference between these species has been always investigated using phenotypic attributes; only Ata et al (2017) investigated the relationships of 12 species belonging to Asteraceae, including G. coronaria and G. discolor, using ITS sequence barcoding. They affirm that the analysed species could be distinctly separated on the genetic basis.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results showed that the G. coronaria and G. discolor can be distinguished using these markers, but further studies with a higher number of molecular markers are needed to confirm it. The genetic difference between these species has been always investigated using phenotypic attributes; only Ata et al (2017) investigated the relationships of 12 species belonging to Asteraceae, including G. coronaria and G. discolor, using ITS sequence barcoding. They affirm that the analysed species could be distinctly separated on the genetic basis.…”
Section: Resultsmentioning
confidence: 99%